Retrograde intrarenal surgery versus percutaneous nephrolithotomy for treatment of renal pelvic stone more than 2 centimeters: a prospective randomized controlled trial - Fayad, Maged Kamal; Fahmy, Omar; Abulazayem, Khaled Mukhtar; Salama, Nashaat M. (Springer, 2021)
This study aimed at investigating the efficacy and safety of retrograde intrarenal surgery (RIRS) in treatment of renal pelvic stone larger than 2 cm against the percutaneous nephrolithotomy (PCNL). Between March 2018 and December 2020, 121 patients were randomized to undergo PCNL (60 patients), or RIRS (61 patients). Both groups were compared in terms of operative time, intraoperative complications. Postoperative complications were assessed based on Clavien–Dindo grading system. Stone-free rates were evaluated by CT scan 6 weeks after surgery. No significant difference were observed between both groups in perioperative criteria. The main operative time was slightly longer in PCNL group (105 vs 95 min, p = 0.49). Stone clearance was higher in PCNL, yet the difference was not significant. (53 patients in PCNL group had either complete clearance or residual fragments < 4 mm, compared to 49 in RIRS group (p = 0.22). Blood transfusion rate was 8.3% in PCNL compared to 1.6% in RIRS group, with a trend towards significance (p = 0.08). Post-operative fever was higher in RIRS, yet it fell just short of statistical significance (13.1% vs 5.0%, p = 0.12). Compared to PCNL, RIRS displayed acceptable efficacy with less risk of bleeding requiring transfusion. It can be applied to patients with large renal pelvic stone as an alternative to PCNL.